Venous thromboembolism rates remained unchanged in operative lower extremity orthopaedic trauma patients from 2008 to 2016. Issue 10 (October 2019) - Warren, Jared A.; Sundaram, Kavin; Hampton, Robert; Billow, Damien; Patterson, Brendan; Piuzzi, Nicolas S.
Highlights: VTE incidence in hip fractures was 1.7% from 2008 to 2016 and did not change significantly during the study period. VTE incidence in femur fractures was 2.4% from 2008 to 2016 and did not change significantly during the study period. VTE incidence in patella fractures was 0.9% from 2008 to 2016 and did not change significantly during the study period. VTE incidence in tibia and/or fibula fractures was 1.1% from 2008 to 2016 and did not change significantly during the study period. VTE incidence in ankle fractures was 0.6% from 2008 to 2016 and did not change significantly during the study period. Abstract: Background: Venous thromboembolism (VTE) is a serious complication that contributes to morbidity, mortality, and healthcare costs during the surgical care of patient with lower extremity fractures. Despite this, few recommendations on the topic exist and the literature on VTE incidence is incomplete. Therefore, this study will attempt to estimate annual incidence and trends in 30-day thrombotic events and mortality for the following fractures: (1) hip, (2) femur, (3) patella, (4) tibia and/or fibula, and (5) ankle. Methods: We identified 120, 521 operative lower extremity orthopaedic trauma patients from 2008 to 2016 using the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database. To evaluate the relationship between the year in which surgery was performed and comorbidities and demographic information bivariate analysis was performed. Bivariate analysis was also performed for the outcomes of interest and year in which the surgery was performed to assess for change. Additionally, bimodal multivariate logistic regression models for hip, femur, and ankle fractures were built, comparing the years 2009 to 2016 using 2008 as a baseline. Results: Overall incidence for VTE over the study period was 1.7% for hip fractures, 2.4% for femur fractures, 0.9% for patella fractures, 1.1% in tibia and/or fibula fractures, and 0.6% in ankle fractures. Over the study period VTE incidence saw a significant decrease (p < 0.05) in hip and femur fractures, but not for patella, tibia and/or fibula, and ankle fractures. After adjusting for confounding factors with multivariate analysis, the change in hip and femur fractures was no longer significant, while no significant decrease was again found for ankle fractures (p > 0.05). Conclusion: Our study demonstrates that VTE rates have remained unchanged in operative lower extremity orthopaedic trauma from 2008 to 2016. This highlights the need for higher quality evidence on this important topic in orthopaedic trauma, including a reevaluation on the necessity of thromboprophylaxis guidelines. Level of Evidence: III.